A Bibliometric Analysis of Artificial Intelligence and Blockchain Technology in Fraud Prevention and Detection - Jannah, Richatul; Sari, Maylia Pramono; Utaminingsih, Nanik Sri; Budiantoro, Risanda Alirastra (Akuisisi : Jurnal Akuntansi, 2024)
This research aims to describe the evolution of publication activity, expand knowledge, identify the most representative authors and journals, and offer insights into potential new directions, especially regarding artificial intelligence and blockchain technology in fraud prevention and detection. This article presents an examination of the development and future trajectory of certain research trends through bibliometric analysis. This analysis involves identifying various research areas within an emerging field and visualizing the bibliometric network using R-bibliophily and Vos Viewer for citation matrices and sensitivity analysis. The data used in this research are around 83 documents consisting of 27 articles, 2 books, 8 book chapters, 29 conference papers, 10 conference reviews, 1 editorial, 1 note, and 5 review results published from 2017 to 2023. Based on World Collaboration Map data shows that there is 1 cooperation data from Chinese researchers to Indonesia and 1 from Indonesia to Australia, so it is hoped that this research can provide a reference, especially for Indonesian writers who will carry out international publications with similar themes.